2018
DOI: 10.4491/eer.2018.127
|View full text |Cite
|
Sign up to set email alerts
|

Microbial population dynamics in constructed wetlands: Review of recent advancements for wastewater treatment

Abstract: Constructed wetlands are improvised man-made systems, designed for adopting the principle of natural wetlands for purifying wastewaterthe elixir of life. They are used widely as a cost-effective and energy-efficient solution for treating greywater generated from different tertiary treatment sources. It provides an elaborate platform for research activities in an attempt to recycle earth's natural resources. Among the several organic impurities removal mechanisms existing in constructed wetland systems, the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 101 publications
(131 reference statements)
1
18
0
1
Order By: Relevance
“…Substrate Type, size, shape, pore spaces, chemical composition, and permeability affect the performance of CW (Gorgoglione and Torretta 2018). CW is not only efficient in removing biodegradable waste but also non-biodegradable pollutants like P and other heavy metals (Rajan et al 2018). The most commonly used substrate materials in CW are soil, sand, gravel, crushed rock, and other natural materials; these materials are efficient in BOD removal but not heavy metals (Qomariyah et al 2016;Haynes 2015).…”
Section: Substratementioning
confidence: 99%
“…Substrate Type, size, shape, pore spaces, chemical composition, and permeability affect the performance of CW (Gorgoglione and Torretta 2018). CW is not only efficient in removing biodegradable waste but also non-biodegradable pollutants like P and other heavy metals (Rajan et al 2018). The most commonly used substrate materials in CW are soil, sand, gravel, crushed rock, and other natural materials; these materials are efficient in BOD removal but not heavy metals (Qomariyah et al 2016;Haynes 2015).…”
Section: Substratementioning
confidence: 99%
“…Study on microbial population dynamics in constructed wetlands, a detailed review of recent advancements for wastewater treatment was concluded and it was demonstrated that microbial population is an important factor in CWs (Rajan et al, 2019). Constructed wetlands and phytoremediation are known as a tool for pharmaceutical removal (Carvalho, 2021).…”
Section: Role Of Microbial Communities and Plants In Constructed Wetlands For Antibiotics Removalmentioning
confidence: 99%
“…Microorganisms are a crucial component of both centralized and decentralized wastewater treatment systems because they remove nitrogenous compounds, phosphate, sulfur, and organic matter, among other pollutants [15]. For instance, nitrogen removal within CW is achieved by microbial processes such as nitrification, denitrification, anaerobic ammonium oxidation (anammox), and complete oxidation of ammonia (comammox) [16].…”
Section: Introductionmentioning
confidence: 99%